Futuros professores que ensinarão matemática: espaços formativos como desencadeadores de novos sentidos sobre a docência - Klein, Maiara Luisa (2020)
This research, linked to the line of Teaching, Knowledge and Professional Development, of the Graduate Program in Education at the Federal University of Santa Maria (UFSM), aims to understand the learning that emerges from the actions of future teachers who will teach mathematics, from the Special Education, Mathematics and Pedagogy courses, from the development of a training space on quantities and measures. Therefore, the Historical-Cultural Theory (THC), the Activity Theory (TA) and the Teaching Guiding Activity (AOE) were the guiding principle, a theoretical contribution that leads to the understanding of the human as a historical being that develops through social interactions. Understanding that the future teacher becomes a teacher because of the relationships he establishes, it was sought to promote a formative space, organized based on an activity-oriented project entitled “Measures in Elementary Education: what is taught at school?”, with a workload of 80 hours, distributed in 14 face-to-face, supervised and unsupervised remote meetings, thus arranged due to the pandemic caused by the Covid-19. 11 students from the Special Education, Mathematics and Pedagogy courses participated in this space. In view of the executing dimension of this research, the data from the records - writings, recordings (audios and videos) - were analyzed, establishing three units that aim to apprehend the phenomenon in its entirety: 1) Initial approaches; 2) Knowledge to teach Mathematics; 3) The formative space as a promoter of quality change. The results showed that, regarding the first unit - recognizing the approximations of future teachers with the teaching and learning process of Mathematics in the initial and final years of Elementary School - the understandings about teaching and the needs arising from initial formation mobilize the future teacher to seek other spaces that bring him closer to the knowledge of Basic Education. As for the second unit - identifying knowledge listed by future teachers as essential for the teaching of mathematics, more specifically on quantities and measures - the understanding was evidenced that, in order to develop an efficient planning, both specific knowledge of the area and those related to teaching are necessary. As for the third unit - understanding sharing within the formative space as a promoter of better teaching quality - the interactions between the three Degree courses - Special Education, Mathematics and Pedagogy - were seen as a possibility for collective syntheses to be promoted, which it can lead to new attributions of meaning about teaching. Therefore, it was concluded that the formative space can promote the appropriation of theoretical knowledge that lead the future teacher to attribute new meanings to his education, teaching and the teaching mathematics, triggering new qualities for his actions.